Electrochemical device and electronic device
By using a double-layer coating structure in the positive electrode sheet of the lithium-ion battery and adding a specific compound of formula I to the electrolyte, the problems of structural degradation and capacity attenuation of the lithium-ion battery during the cycle are solved, and electrochemical performance with high safety and long life are achieved.
Patent Information
- Application Number
- CN202510005947.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-02
AI Technical Summary
Existing lithium-ion batteries have problems of structural degradation and capacity attenuation during the circulation process, and their safety performance is insufficient, making it difficult to meet the high safety and long life requirements of lightweight and portable electronic products.
By adopting a double-layer coating structure in the positive electrode sheet of the electrochemical device, the inner positive electrode material layer contains high manganese elements, the outer positive electrode material layer contains low or no manganese elements, and adding a specific compound of formula I to the electrolyte, it can bind to Lewis acid, remove Lewis acid, inhibit the dissolution of transition metals, and form a good SEI film on the negative electrode, improving film formation stability and structural stability.
It effectively improves the circulation, storage and safety performance of electrochemical devices, extends battery life, and reduces safety risks.
Smart Images

Figure SMS_1 
Figure SMS_9 
Figure SMS_10
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to an electrochemical device and an electronic device. Background Art
[0002] With the popularization and application of smart products, people's demand for electronic products such as mobile phones, laptops, cameras, etc. has increased year by year. As the working power source of electronic products, lithium-ion batteries have the characteristics of high energy density, no memory effect, and high working voltage, and are gradually replacing traditional Ni-Cd and MH-Ni batteries. However, with the development of electronic products towards thinness and portability, people's requirements for lithium-ion batteries are constantly increasing, and the development of highly safe and long-life lithium-ion batteries is one of the main demands of the market. Summary of the invention
[0003] The purpose of this application is to provide an electrochemical device and an electronic device to improve the cycle performance, storage performance and safety performance of the electrochemical device. The specific technical solution is as follows:
[0004] The first aspect of the present application provides an electrochemical device, which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the electrolyte includes at least one compound of formula I:
[0005] In the compound of formula I, R 11 and R 12 are each independently selected from a hydrogen atom, a halogen atom, a substituted or unsubstituted C 1 To C 10 Alkyl, substituted or unsubstituted C 2 To C 10 Alkenyl, substituted or unsubstituted C 2 To C 10 Alkynyl, substituted or unsubstituted C 1 To C 10 Alkoxy or substituted or unsubstituted C 1 To C 10 acyloxy; when substituted, the substituent is selected from halogen atoms, C 2 To C 5 Cycloalkyl or C 6 To C 12 Aromatic group.
[0006] In the compound of formula I, X 11 ¯Anionic group is selected from PF 6 ¯, F¯, NO 3 ¯,PO 2 F 2 ¯, BF 4 ¯、(FSO 2 )2 N¯, F 3 SO 2 O¯, , , , , , or Any of;
[0007] Based on the mass of the electrolyte, the mass percentage of the compound of formula I is x%, 0.01≤x≤5; the positive electrode sheet comprises a positive electrode current collector and a first positive electrode material layer and a second positive electrode material layer located on at least one surface of the positive electrode current collector, the first positive electrode material layer is located between the positive electrode current collector and the second positive electrode material layer, the first positive electrode material layer comprises a Mn element and has a thickness of h 1 μm, the thickness of the second positive electrode material layer is h 2 μm, where the thickness of the first positive electrode material layer is h 1 and the thickness of the second positive electrode material layer h 2 The ratio h 1 / h 2 is k; x and h 1 Satisfying the relationship: 0.00033≤x / h 1 ≤0.1. By adjusting the type and mass percentage of the compound of formula I and the ratio of the content of the compound of formula I to the thickness of the first positive electrode material layer x / h 1 , within the scope of this application, can effectively improve the film formation stability on the positive and negative electrode surfaces, the structural stability of the positive electrode sheet, and reduce Mn 2+ dissolution, thereby effectively improving the cycle performance, storage performance and safety performance of the electrochemical device.
[0008] In one embodiment of the present application, the electrochemical device satisfies at least one of the following characteristics: (1) 30 ≤ h 1 ≤200; (2) 0.5≤k≤150; (3) 0.005≤x / h 1 ≤0.1. By adjusting the thickness of the first positive electrode material layer, k or x / h 1 The value of satisfies at least one of the above characteristics, which can improve the cycle performance, storage performance and safety performance of the electrochemical device.
[0009] In one embodiment of the present application, the compound of formula I includes at least one of the following compounds: .
[0010] The compound of formula I is selected. The compound of formula I can combine with Lewis acid and effectively remove Lewis acid, such as HF or PF. 5 , inhibiting the dissolution of transition metals from the positive electrode caused by Lewis acid; and forming a better SEI film at the negative electrode to prevent the decomposition of the electrolyte due to the destruction of the film, and can effectively improve the film formation stability on the positive and negative electrode surfaces and the structural stability of the positive electrode sheet, so that the electrochemical device has good cycle performance, storage performance and safety performance.
[0011] In one embodiment of the present application, the electrolyte further comprises a silane compound containing an unsaturated bond, and the silane compound containing an unsaturated bond is selected from at least one of the compounds of formula II:
[0012] Among them, R 21 , R 22 , R 23 and R 24 are each independently selected from a hydrogen atom, a halogen atom, a cyano group, a substituted or unsubstituted C 1 To C 10 Alkyl, substituted or unsubstituted C 2 To C 10 Alkenyl, substituted or unsubstituted C 2 To C 10 Alkynyl, substituted or unsubstituted C 1 To C 10 Any one of the heteroatom-containing functional groups of R, when substituted, the substituent is a halogen atom; the heteroatom is selected from Si or O; R 21 , R 22 , R 23 and R 24 Any two groups in can form a ring; 21 , R 22 , R 23 and R 24 At least one of them contains an unsaturated bond; based on the mass of the electrolyte, the mass percentage of the compound of formula II is f%, 0.01≤f≤1, and the cycle performance, storage performance and safety performance of the electrochemical device can be improved within the scope of this application by regulating the type and mass percentage of the compound of formula II.
[0013] In one embodiment of the present application, the compound of formula II includes at least one of tetramethyl divinyl disiloxane, maleic acid bis (trimethylsilyl) ester, tetraallyl silane, pentamethyl pentavinyl cyclopentasiloxane, vinyl trimethyl silane, divinyl dimethyl silane, 1,3-dimethyl-1,1,3,3-tetravinyl disiloxane, trivinyl methyl silane, triethyl vinyl silane, allyl triethoxy silane, triethyl silyl acetylene, tetravinyl silane, triacetoxy ethyl silane, tetramethyl tetravinyl cyclotetrasiloxane, diphenyl difluorosilane, 2,4,6-trivinyl-2,4,6-trimethyl cyclotrisiloxane or vinyl triethoxy silane. The above-mentioned compound of formula II is selected to improve the chemical stability of the electrolyte, thereby further improving the cycle performance, storage performance and safety performance of the electrochemical device.
[0014] In one embodiment of the present application, the first positive electrode material layer includes a first positive electrode active material, the first positive electrode active material includes at least one of lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium manganese iron phosphate, lithium manganese phosphate or lithium-rich manganese-based materials, and the mass percentage of the Mn element in the first positive electrode material layer is y based on the mass of the first positive electrode material layer. 1 %,20≤y 1 ≤60. By adjusting the type of the first positive electrode active material and the mass percentage of the Mn element within the scope of this application, the first positive electrode material layer has a suitable Mn element content, which can reduce the Mn 2+ dissolution, thereby improving the cycle performance, storage performance and safety performance of the electrochemical device.
[0015] In one embodiment of the present application, the second positive electrode material layer includes a second positive electrode active material, and the second positive electrode active material includes at least one of lithium cobaltate, lithium iron phosphate, lithium manganese iron phosphate, lithium manganese phosphate, sodium iron phosphate, lithium vanadium phosphate, sodium vanadium phosphate, lithium vanadium oxyphosphate, sodium vanadium oxyphosphate, lithium vanadate, lithium nickelate, lithium nickel cobalt manganese oxide, lithium-rich manganese-based material, lithium nickel cobalt aluminum oxide or lithium titanate, and the mass percentage of Mn element in the second positive electrode material layer is y based on the mass of the second positive electrode material layer. 2 %,y 1 >y 2 By adjusting the type of the second positive electrode active material and the mass percentage of the Mn element within the scope of this application, the mass percentage of the Mn element in the second positive electrode material layer is less than that in the first positive electrode material layer, which can reduce the contact area between the first positive electrode material layer and the electrolyte, and reduce the Mn element content in the first positive electrode material layer. 2+ dissolution, thereby further improving the cycle performance, storage performance and safety performance of the electrochemical device.
[0016] In one embodiment of the present application, the first positive electrode material layer includes a first positive electrode active material, which includes at least one of lithium manganese oxide or lithium iron manganese phosphate; the second positive electrode material layer includes a second positive electrode active material, which includes at least one of lithium iron phosphate or lithium nickel cobalt manganese oxide.
[0017] In one embodiment of the present application, the electrolyte includes a cyclic carbonate compound, and the mass percentage of the cyclic carbonate compound is z%, 5≤z≤40 based on the mass of the electrolyte. By regulating the mass percentage of the cyclic carbonate compound within the scope of the present application, the cycle performance, storage performance and safety performance of the electrochemical device can be improved.
[0018] In one embodiment of the present application, based on the thickness h of the first positive electrode material layer 1 , 1.25≤h 1 / z≤30. By regulating h 1 The value of / z within the scope of the present application can further improve the cycle performance, storage performance and safety performance of the electrochemical device.
[0019] In one embodiment of the present application, the cyclic carbonate compound includes at least one of ethylene carbonate, propylene carbonate or butylene carbonate. By regulating the type of cyclic carbonate compound within the scope of the present application, the cycle performance, storage performance and safety performance can be further improved.
[0020] A second aspect of the present application provides an electronic device, which includes the electrochemical device in any of the aforementioned embodiments.
[0021] Beneficial effects of this application:
[0022] The present application provides an electrochemical device, which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the electrolyte includes a compound of formula I, and the mass percentage of the compound of formula I is x%, based on the mass of the electrolyte, 0.01≤x≤5; the positive electrode sheet includes a positive electrode current collector and a first positive electrode material layer and a second positive electrode material layer located on at least one surface of the positive electrode current collector, the first positive electrode material layer is located between the positive electrode current collector and the second positive electrode material layer, the first positive electrode material layer includes a Mn element and has a thickness of h 1 μm, the thickness of the second positive electrode material layer is h 2 μm, x and h 1 Satisfying the relationship: 0.00033≤x / h 1 ≤0.1. The positive electrode double-layer coating has a higher manganese content in the inner positive electrode material layer and a lower manganese content or no manganese in the outer positive electrode material layer, which can reduce the contact between the manganese-containing material and the electrolyte and reduce Mn 2+Dissolution. The compound represented by formula I can combine with Lewis acid, effectively remove Lewis acid, and inhibit the dissolution of transition metals from the positive electrode caused by Lewis acid; the compound represented by formula I can also form a good SEI film at the negative electrode to prevent the decomposition of the electrolyte due to the destruction of the film.
[0023] By adjusting the thickness h of the compound represented by formula I and the first positive electrode material layer 1 , control x / h 1 The value of is within the scope of this application, which can effectively improve the film formation stability on the positive and negative electrode surfaces, the structural stability of the positive electrode sheet, and reduce the Mn 2+ dissolution, thereby effectively improving the cycle performance, storage performance and safety performance of the electrochemical device.
[0024] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical scheme, and advantages of the present application more clearly understood, the present application is further described in detail with reference to the following embodiments. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0026] It should be noted that in the specific implementation manner of the present application, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the secondary battery of the present application is not limited to a lithium-ion battery.
[0027] The present application provides an electrochemical device, which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the electrolyte includes at least one compound of formula I:
[0028] Among them, R 11 and R 12 are each independently selected from a hydrogen atom, a halogen atom, a substituted or unsubstituted C 1 To C 10 Alkyl, substituted or unsubstituted C 2 To C 10 Alkenyl, substituted or unsubstituted C 2 To C 10 Alkynyl, substituted or unsubstituted C 1 To C 10 Alkoxy or substituted or unsubstituted C 1 To C 10 acyloxy; when substituted, the substituent is selected from halogen atoms, C 2 To C 5 Cycloalkyl or C6 To C 12 Aromatic group;
[0029] X 11 ¯Anionic group is selected from PF 6 ¯, F¯, NO 3 ¯,PO 2 F 2 ¯, BF 4 ¯、(FSO 2 ) 2 N¯, F 3 SO 2 O¯, , , , , , or Any of;
[0030] Based on the mass of the electrolyte, the mass percentage of the compound of formula I is x%, 0.01≤x≤5, illustratively, the value of x can be 0.01, 0.2, 0.4, 0.6, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8, 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, 3.2, 3.4, 3.6, 3.8, 4.0, 4.2, 4.4, 4.6, 4.8, 5.0 or a range consisting of any two of the above values; the positive electrode sheet comprises a positive electrode collector and a first positive electrode material layer and a second positive electrode material layer located on at least one surface of the positive electrode collector, the first positive electrode material layer is located between the positive electrode collector and the second positive electrode material layer, the first positive electrode material layer comprises an Mn element and has a thickness of h 1 μm, the thickness of the second positive electrode material layer is h 2 μm, where the thickness of the first positive electrode material layer is h 1 and the thickness of the second positive electrode material layer h 2 The ratio h 1 / h 2 is k; x and h 1 Satisfying the relationship: 0.00033≤x / h 1 ≤0.1, illustratively, x / h 1 The value of can be 0.00033, 0.0006, 0.0009, 0.003, 0.006, 0.009, 0.03, 0.06, 0.09, 0.3, 0.6, 0.9, 1.0 or a range consisting of any two of the above values.
[0031] The inventors have found that lithium manganese oxide materials are usually used as positive electrode active materials for electrochemical devices due to their abundant and cheap manganese raw materials, simple synthesis process, low price, easy industrial production, low environmental pollution and good safety performance. However, during the electrochemical cycle, direct contact between the electrolyte and the positive electrode material will cause the high-valent manganese ions to be reduced and precipitated Mn 2+ ions, manganese loss in active materials, leading to structural degradation and capacity decay of the electrode. The positive electrode double-layer coating, the first positive electrode material layer with a higher manganese content is coated on the inner layer, which can reduce the contact between the first positive electrode material layer and the electrolyte and reduce Mn 2+ In addition, the compound shown in Formula I added to the electrolyte can combine with Lewis acid and effectively remove Lewis acid, such as HF or PF. 5 , inhibiting the dissolution of transition metals from the positive electrode caused by Lewis acid. At the same time, the compound of formula I can also form a good SEI film at the negative electrode to prevent the decomposition of the electrolyte due to the destruction of the film. Therefore, by regulating the type and coating method of the positive electrode material layer and the type and mass percentage of the compound of formula I within the scope of this application, the electrochemical device can have good cycle performance, storage performance and safety performance.
[0032] In one embodiment of the present application, the thickness of the first positive electrode material layer is h 1 μm, 30≤h 1 ≤200. For example, h 1 The value of can be 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150, 155, 160, 165, 170, 175, 180, 185, 190, 195, 200 or a range consisting of any two of the above values. By adjusting the thickness of the first positive electrode material layer, the contact between the manganese-containing material and the electrolyte can be reduced and the Mn 2+ dissolution, thereby improving the cycle performance, storage performance and safety performance of the secondary battery.
[0033] In one embodiment of the present application, the thickness of the first positive electrode material layer is 1 μm and the thickness of the second positive electrode material layer h 2 The ratio of μm h 1 / h 2k, 0.5≤k≤150. Exemplarily, the value of k can be 0.5, 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150 or a range consisting of any two of the above values. By adjusting the ratio k within the scope of this application, the structure of the positive electrode active material layer can be optimized, so that the electrochemical device has good cycle performance, storage performance and safety performance.
[0034] In one embodiment of the present application, 0.005≤x / h 1 ≤0.1. For example, x / h 1 The value of can be 0.005, 0.01, 0.015, 0.02, 0.025, 0.03, 0.035, 0.04, 0.045, 0.05, 0.055, 0.06, 0.065, 0.07, 0.075, 0.08, 0.085, 0.09, 0.095, 0.1 or a range consisting of any two of the above values. By adjusting the content of the compound represented by formula I and the thickness of the first positive electrode material layer, the ratio x / h 1 , control x / h 1 The value of is within the above range, preferably the mass percentage of the compound of formula I and the thickness of the first positive electrode material layer make x / h 1 With a suitable value, it can further improve the film formation stability on the positive and negative electrode surfaces and the structural stability of the positive electrode sheet, and further reduce Mn 2+ dissolution, thereby further improving the cycle performance, storage performance and safety performance of the electrochemical device.
[0035] In one embodiment of the present application, the compound of formula I includes at least one of the following compounds: .
[0036] The compound of formula I is selected. The compound of formula I can combine with Lewis acid and effectively remove Lewis acid, such as HF or PF. 5, inhibiting the dissolution of transition metals from the positive electrode caused by Lewis acid; and forming a better SEI film at the negative electrode to prevent the decomposition of the electrolyte due to the destruction of the film, and can effectively improve the film formation stability on the positive and negative electrode surfaces and the structural stability of the positive electrode sheet, so that the electrochemical device has good cycle performance, storage performance and safety performance.
[0037] In one embodiment of the present application, the electrolyte further comprises a silane compound containing an unsaturated bond, and the silane compound containing an unsaturated bond is selected from at least one of the compounds of formula II:
[0038] Among them, R 21 , R 22 , R 23 and R 24 are each independently selected from a hydrogen atom, a halogen atom, a cyano group, a substituted or unsubstituted C 1 To C 10 Alkyl, substituted or unsubstituted C 2 To C 10 Alkenyl, substituted or unsubstituted C 2 To C 10 Alkynyl, substituted or unsubstituted C 1 To C 10 Any one of the heteroatom-containing functional groups of R, when substituted, the substituent is a halogen atom; the heteroatom is selected from Si or O; R 21 , R 22 , R 23 and R 24 Any two groups in can form a ring; 21 , R 22 , R 23 and R 24 At least one of them contains an unsaturated bond. The compound of formula II can form a protective film on the surface of the negative electrode, reduce the occurrence of reduction reaction, and further improve the cycle performance, storage performance and safety performance of the electrochemical device.
[0039] In one embodiment of the present application, the mass percentage of the compound of formula II is f%, and 0.01≤f≤1. Exemplarily, the value of f can be 0.01, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1 or a range consisting of any two of the above values. By regulating the mass percentage of the compound of formula II within the scope of the present application, the chemical stability of the electrolyte can be improved, thereby further improving the cycle performance, storage performance and safety performance of the electrochemical device.
[0040] In one embodiment of the present application, the compound of formula II includes at least one of tetramethyl divinyl disiloxane, maleic acid bis (trimethylsilyl) ester, tetraallyl silane, pentamethyl pentavinyl cyclopentasiloxane, vinyl trimethyl silane, divinyl dimethyl silane, 1,3-dimethyl-1,1,3,3-tetravinyl disiloxane, trivinyl methyl silane, triethyl vinyl silane, allyl triethoxy silane, triethyl silyl acetylene, tetravinyl silane, triacetoxy ethyl silane, tetramethyl tetravinyl cyclotetrasiloxane, diphenyl difluorosilane, 2,4,6-trivinyl-2,4,6-trimethyl cyclotrisiloxane or vinyl triethoxy silane. The above-mentioned compound of formula II is selected to improve the chemical stability of the electrolyte, thereby further improving the cycle performance, storage performance and safety performance of the electrochemical device.
[0041] In one embodiment of the present application, the first positive electrode material layer includes a first positive electrode active material, the first positive electrode active material includes at least one of lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium manganese iron phosphate, lithium manganese phosphate or lithium-rich manganese-based materials, and based on the mass of the first positive electrode material layer, the mass percentage of the Mn element in the first positive electrode material layer is y 1 %, 20≤y≤60. For example, y 1 The value of can be 20, 22, 24, 26, 28, 30, 32, 34, 36, 38, 40, 42, 44, 46, 48, 50, 52, 54, 56, 58, 60 or a range consisting of any two of the above values. By adjusting the type of the first positive electrode active material and the mass percentage of the Mn element in the first positive electrode material layer y 1 % Within the scope of this application, the first positive electrode active material can have a suitable Mn element content, so that the first positive electrode material layer reduces Mn in contact with the electrolyte. 2+ dissolution, thereby effectively improving the cycle performance, storage performance and safety performance of the electrochemical device.
[0042] In one embodiment of the present application, the second positive electrode material layer includes a second positive electrode active material, and the second positive electrode active material includes at least one of lithium cobalt oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium manganese phosphate, sodium iron phosphate, lithium vanadium phosphate, sodium vanadium phosphate, lithium vanadium oxyphosphate, sodium vanadium oxyphosphate, lithium vanadate, lithium nickel oxide, lithium nickel cobalt manganese oxide, lithium-rich manganese-based material, lithium nickel cobalt aluminum oxide or lithium titanate, and the mass percentage of Mn element in the second positive electrode material layer is y based on the mass of the second positive electrode material layer. 2 %,y 1 >y 2 By adjusting the type of the second positive electrode active material and the mass percentage of the Mn element in the second positive electrode material layer within the scope of the present application, the mass percentage of the Mn element in the second positive electrode material layer can be adjusted to y2 Less than y 1 , which is different from the first positive electrode material layer. The second positive electrode material layer has a smaller Mn content, and less Mn is precipitated when in contact with the electrolyte. 2+ , and the second positive electrode material layer can reduce the contact area between the first positive electrode material layer and the electrolyte, thereby reducing the Mn 2+ dissolution, further improving the cycle performance, storage performance and safety performance of the electrochemical device.
[0043] In one embodiment of the present application, the first positive electrode material layer includes a first positive electrode active material, the first positive electrode active material includes at least one of lithium manganese oxide or lithium iron manganese phosphate; the second positive electrode material layer includes a second positive electrode active material, the second positive electrode active material includes at least one of lithium iron phosphate or lithium nickel cobalt manganese oxide. By regulating the types of the first positive electrode active material and the second positive electrode active material within the scope of the present application, the cycle performance, storage performance and safety performance of the electrochemical device can be further improved.
[0044] In one embodiment of the present application, the electrolyte further comprises a cyclic carbonate compound, and the mass percentage of the cyclic carbonate compound is z%, 5≤z≤40, based on the mass of the electrolyte. Exemplarily, the value of z can be 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40 or a range consisting of any two of the above values. By regulating the mass percentage of the cyclic carbonate compound within the scope of the present application, the cycle performance, storage performance and safety performance of the electrochemical device can be improved.
[0045] In one embodiment of the present application, the thickness of the first positive electrode material layer is 1 The ratio of μm to the mass percentage of cyclic carbonate compound is z% is h 1 / z,1.25≤h 1 / z≤30. For example, h 1 The value of / z can be 1.25, 2.5, 3.75, 5, 6.25, 7.5, 8.75, 10, 11.25, 12.5, 13.75, 15, 16.25, 17.5, 18.75, 20, 21.25, 22.5, 23.75, 25, 26.25, 27.5, 28.75, 30 or a range consisting of any two of the above values. 1 The value of / z within the scope of the present application can further improve the cycle performance, storage performance and safety performance of the electrochemical device.
[0046] In one embodiment of the present application, the cyclic carbonate compound includes at least one of ethylene carbonate, propylene carbonate or butylene carbonate. By regulating the type of the cyclic carbonate compound within the scope of the present application, the cycle performance, storage performance and safety performance of the electrochemical device can be further improved.
[0047] In the present application, the features of the different components contained in the above-mentioned electrolyte can be combined, and the implementation modes covered by the above-mentioned combination are all within the protection scope of the present application.
[0048] In the present application, the electrolyte also includes a lithium salt and a non-aqueous organic solvent. The present application has no particular restrictions on the lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to LiPF 6 , LiBF 4 、LiAsF 6 、LiClO 4 、LiB(C 6 H 5 ) 4 、LiCH 3 SO 3 、LiCF 3 SO 3 、LiN(SO 2 CF 3 ) 2 、LiC(SO 2 CF 3 ) 3 , Li 2 SiF 6, lithium bis(oxalatoborate) (LiBOB) or lithium difluoroborate. The present application has no particular restrictions on the content of lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. For example, based on the mass of the electrolyte, the mass percentage of lithium salt is 8% to 15%. The present application has no particular restrictions on non-aqueous solvents, as long as the purpose of the present application can be achieved. For example, non-aqueous solvents may include but are not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of chain carbonate compounds or fluorocarbonate compounds. The above-mentioned chain carbonate compounds may include but are not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (MEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application does not particularly limit the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved. For example, the mass percentage of the non-aqueous solvent is 40% to 90%.
[0049] In the present application, the electrochemical device also includes a positive electrode plate, which includes a positive electrode collector and a positive electrode material layer arranged on at least one surface of the positive electrode collector. The above-mentioned "positive electrode material layer arranged on at least one surface of the positive electrode collector" means that the positive electrode material layer can be arranged on one surface of the positive electrode collector along the thickness direction of itself, or on two surfaces of the positive electrode collector along the thickness direction of itself. It should be noted that the "surface" here can be the entire area of the positive electrode collector or a partial area of the positive electrode collector. This application has no special restrictions, as long as the purpose of this application can be achieved. This application has no special restrictions on the positive electrode collector, as long as the purpose of this application can be achieved. For example, it can include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).
[0050] The positive electrode material layer of the present application also includes a conductive agent and a binder. The present application has no special restrictions on the conductive agent and binder in the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of conductive carbon black, carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers. The above-mentioned conductive carbon black may include but is not limited to Super P, acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nanocarbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymer may include but is not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. The binder may include, but is not limited to, at least one of polyacrylate, polyimide, polyamide, polyamideimide, polyvinylidene fluoride, polystyrene butadiene copolymer (styrene butadiene rubber, SBR), sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, sodium carboxymethyl cellulose (CMC-Na), potassium carboxymethyl cellulose, sodium hydroxymethyl cellulose or potassium hydroxymethyl cellulose. The present application does not particularly limit the mass ratio of the positive electrode active material, the conductive agent, and the binder in the positive electrode material layer. Those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.
[0051] The present application has no particular limitation on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness of the positive electrode current collector is 1 μm to 20 μm. The present application has no particular limitation on the thickness of the positive electrode material layer, as long as the purpose of the present application can be achieved, for example, the thickness of the single-sided positive electrode material layer is 30 μm to 120 μm.
[0052] Optionally, the positive electrode plate may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be at least one of the above conductive agent and the above binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.
[0053] In the present application, the electrochemical device also includes a negative electrode plate, which includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the negative electrode current collector or a partial area of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. This application has no special restrictions on the negative electrode current collector, as long as the purpose of this application can be achieved. For example, it can include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector, etc.
[0054] The negative electrode material layer of the present application includes a negative electrode active material. The present application has no particular limitation on the negative electrode active material, as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO x (0.5<x<1.6), silicon oxygen carbon materials, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO 2 , spinel structure lithium titanate Li 4 Ti 5 O 12, Li-Al alloy or metallic lithium, etc. The negative electrode material layer of the present application also includes a binder. The present application has no special restrictions on the binder in the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the binder can be at least one of the above binders. The negative electrode material layer of the present application also includes a conductive agent. The present application has no special restrictions on the conductive agent in the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the conductive agent can be at least one of the above conductive agents. The negative electrode material layer of the present application also includes a thickener. The present application has no special restrictions on the thickener in the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickener can be sodium carboxymethyl cellulose (CMC-Na). The present application has no special restrictions on the mass ratio of the negative electrode active material, conductive agent, thickener and binder in the negative electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.
[0055] The present application has no particular limitation on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness of the negative electrode current collector is 5 μm to 16 μm. The present application has no particular limitation on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved, for example, the thickness of the single-sided negative electrode material layer is 30 μm to 120 μm.
[0056] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be at least one of the above conductive agent and the above binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.
[0057] In the present application, the electrochemical device also includes a diaphragm. The present application has no particular restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm may include, but is not limited to, polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) films), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The type of diaphragm may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.
[0058] In some embodiments of the present application, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer may be a nonwoven fabric, a film or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.
[0059] Optionally, a surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0060] In some embodiments of the present application, the inorganic layer includes inorganic particles and a binder. The present application is not particularly limited to inorganic particles, such as inorganic particles can include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application is not particularly limited to binders, such as binders can be at least one of the above-mentioned binders. In some embodiments of the present application, the polymer layer includes polymers, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymers, polyacrylic acid, polyacrylates, polyvinyl pyrrolidone, polyvinyl ether or polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).
[0061] The present application has no particular limitation on the thickness of the diaphragm, as long as the purpose of the present application can be achieved. For example, the thickness of the diaphragm may be 3 μm to 30 μm.
[0062] The electrochemical device of the present application also includes a packaging bag for containing a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the art in the electrochemical device, and the present application does not limit the above other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application.
[0063] The present application does not particularly limit the type of electrochemical device, which may include any device that undergoes an electrochemical reaction. In the present application, the electrochemical device may include, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery or a lithium ion polymer secondary battery (lithium ion polymer battery), etc.
[0064] The preparation process of the electrochemical device of the present application is well known to those skilled in the art, and the present application has no particular limitation. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain an electrochemical device; or stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the packaging bag as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.
[0065] The second aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. Therefore, the electronic device provided by the present application has good performance.
[0066] The present application does not particularly limit the type of electronic device, which can be any electronic device known in the prior art. In some embodiments, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0067] Example
[0068] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are by mass.
[0069] Test methods and equipment:
[0070] Cycle performance test:
[0071] Place the lithium-ion battery in a 25℃ constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge the lithium-ion battery that has reached a constant temperature to 4.2V at 25℃ at a constant current of 0.2C, charge it to 0.05C at a constant voltage at 4.2V, let it stand for 5 minutes, then discharge it to 2.8V at a constant current of 0.2C, let it stand for 5 minutes, and test the initial discharge capacity C of the lithium-ion battery. 0; Then charge to 4.2V at 1C constant current, charge to 0.05C at 4.2V; leave for 5 minutes; then discharge to 2.8V at 1C constant current, leave for 5 minutes, this is one charge and discharge cycle. Repeat this charge and discharge cycle to 1000 times, and measure the discharge capacity C of the lithium-ion battery after 1000 cycles 1 .
[0072] Capacity retention after 1000 cycles at 25℃ = C 1 / C 0 ×100%.
[0073] Nail Test
[0074] Take 10 lithium-ion batteries to be tested and charge them at a constant current of 0.5C rate to a voltage of 4.2V at room temperature, and further charge them at a constant voltage of 4.2V to a current of 0.05C, so that they are in a fully charged state of 4.2V. Then, pierce the lithium-ion battery at room temperature, using a nail with a diameter of 2.5mm (steel nail, made of carbon steel, with a taper of 16.5mm, and a total length of 100mm), at a piercing speed of 30mm / s, and the piercing depth is based on the taper of the steel nail passing through the lithium-ion battery. Stay for 5 minutes and observe whether the lithium-ion battery produces smoke, catches fire or explodes. If not, the lithium-ion battery is considered to have passed the nail piercing test.
[0075] High temperature memory impedance (IMP) growth rate test
[0076] Take 3 lithium-ion batteries to be tested and charge them at room temperature (25℃±3℃) at a constant current of 0.5C to a voltage of 4.2V. Then charge them at a constant voltage of 4.2V to a current of 0.05C to make them fully charged at 4.2V. Use an OCV / IMP tester to record the AC impedance of the battery at 1KHz in mΩ, which is recorded as the initial impedance of the battery. Then place them in an oven at 85℃ and store them for 8h. After the end, place the batteries at 25℃±3℃ and let them stand for 2h. Use an OCV / IMP tester to record the AC impedance of the battery at 1KHz in mΩ. Use the initial impedance of the battery as a benchmark to compare the IMP growth rate after storage at 85℃ for 8h.
[0077] Example 1-1
[0078] <Preparation of positive electrode sheet>
[0079] The first positive electrode active material is lithium manganese oxide (LiMn 2 O 4), conductive agent Super P, and binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 97:1.4:1.6, and N-methylpyrrolidone (NMP) was added as a solvent to prepare a slurry with a solid content of 75wt%. After being stirred evenly with a vacuum mixer, the first positive electrode slurry was obtained. The second positive electrode active material lithium cobalt oxide (LiCoO 2 ), conductive agent Super P, and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97:1.4:1.6, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 75wt%. After being stirred evenly by a vacuum mixer, the second positive electrode slurry is obtained. The first positive electrode slurry is coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried at 85°C to obtain a first positive electrode material layer with a thickness of 100μm, and then the second positive electrode slurry is coated on the first positive electrode material layer, and dried at 85°C to obtain a single-sided coated positive electrode sheet with a second positive electrode material layer thickness of 50μm. After that, the above steps are repeated on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided coated positive electrode material layer. After coating, the positive electrode sheet is cold pressed and cut into a specification of 74mm×866m for standby use. Among them, the compaction density of the positive electrode material layer after cold pressing is 3.2g / cm 3 .
[0080] <Preparation of negative electrode sheet>
[0081] The negative electrode active material artificial graphite, conductive agent (Super P), thickener sodium carboxymethyl cellulose, and binder styrene butadiene rubber are mixed in a mass ratio of 96.4:1.5:0.5:1.6, deionized water is added as a solvent, and a slurry with a solid content of 70wt% is prepared. The negative electrode slurry is obtained after being stirred evenly by a vacuum mixer. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 8μm, and dried at 110°C to obtain a negative electrode sheet with a single-sided negative electrode material layer coated with a coating thickness of 110μm. After that, the above steps are repeated on the other surface of the copper foil to obtain a negative electrode sheet with a double-sided negative electrode material layer coated. After the coating is completed, the negative electrode sheet is cold pressed and cut into a specification of 78mm×875mm for standby use. Among them, the compaction density of the negative electrode material layer after cold pressing is 1.70g / cm 3 .
[0082] <Diaphragm>
[0083] Alumina and PVDF were mixed in a mass ratio of 95:5, NMP was added as a solvent, and a slurry with a solid content of 12wt% was prepared, and the mixture was stirred evenly to obtain an inorganic layer slurry; the inorganic layer slurry was evenly coated on one surface of a polyethylene substrate with a thickness of 9μm, and a diaphragm with a single-sided inorganic layer coated thereon with a coating thickness of 2μm was obtained after drying. Then PVDF was added to the NMP solvent and stirred evenly to prepare a polymer layer slurry with a solid content of 25wt%, and then the polymer layer slurry was evenly coated on the surface of the inorganic layer away from the substrate, and dried to obtain a diaphragm with a single-sided inorganic layer and a polymer layer coated thereon; then the polymer layer slurry was evenly coated on the other surface of the polyethylene substrate, and dried to obtain a diaphragm with an inorganic layer and a polymer layer coated on one side and only a polymer layer coated on the other side. Among them, the surface density of the coated polymer layer slurry is 0.15mg / cm 2 .
[0084] <Preparation of Electrolyte>
[0085] In an argon atmosphere glove box with a water content of less than 10 ppm, ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) are mixed to obtain a basic organic solvent, and then lithium hexafluorophosphate is added to the basic organic solvent, dissolved and mixed evenly. Then the compound of formula I-1 is added to obtain a non-aqueous electrolyte. Wherein, based on the mass of the non-aqueous electrolyte, the mass percentage of the lithium salt is 12.5%, the mass percentage of the compound of formula I is 1%, the mass percentage of EC is 20%, the mass percentage of PC is 20%, and the mass percentage of DEC is 46.5%.
[0086] <Preparation of lithium battery>
[0087] The positive electrode sheet, separator, negative electrode sheet and separator prepared above are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer packaging aluminum-plastic film, after dehydration at 80°C, the prepared non-aqueous electrolyte is injected and packaged, and a lithium-ion battery is obtained after standing, forming, degassing, trimming, shaping and capacity testing steps.
[0088] Example 1-2 to Example 1-7
[0089] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.
[0090] Wherein, when the mass percentage x of the compound of formula I changes, the mass percentage of diethyl carbonate changes accordingly, and the mass percentages of lithium salt, ethylene carbonate and propylene carbonate remain unchanged. The sum of the mass percentages of the compound of formula I, lithium salt, ethylene carbonate, propylene carbonate and diethyl carbonate is 100%.
[0091] Examples 1-8
[0092] Except that the positive electrode sheet is prepared according to the following steps in <Preparation of positive electrode sheet>, the rest is the same as Example 1-1.
[0093] <Preparation of positive electrode sheet>
[0094] The first positive electrode active material is lithium manganese oxide (LiMn 2 O 4 ), conductive agent Super P, and binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 97:1.4:1.6, and N-methylpyrrolidone (NMP) was added as a solvent to prepare a slurry with a solid content of 75wt%. After being stirred evenly with a vacuum mixer, the first positive electrode slurry was obtained. The second positive electrode active material lithium cobalt oxide (LiCoO 2 ), conductive agent Super P, and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97:1.4:1.6, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 75wt%. The second positive electrode slurry is obtained after being stirred evenly by a vacuum mixer. The first positive electrode slurry is coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried at 85°C to obtain a first positive electrode material layer with a thickness of 150μm, and then the second positive electrode slurry is sprayed on the first positive electrode material layer with a spray device, and dried at 85°C to obtain a single-sided coated positive electrode sheet with a second positive electrode material layer thickness of 1μm. After that, the above steps are repeated on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided coated positive electrode material layer. After coating, the positive electrode sheet is cold pressed and cut into a specification of 74mm×866m for standby use. Among them, the compaction density of the positive electrode material layer after cold pressing is 3.2g / cm 3 .
[0095] Examples 1-9
[0096] Except that the positive electrode sheet is prepared according to the following steps in <Preparation of positive electrode sheet>, the rest is the same as Example 1-1.
[0097] <Preparation of positive electrode sheet>
[0098] The first positive electrode active material is lithium manganese oxide (LiMn 2 O 4 ), conductive agent Super P, and binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 97:1.4:1.6, and N-methylpyrrolidone (NMP) was added as a solvent to prepare a slurry with a solid content of 75wt%. After being stirred evenly with a vacuum mixer, the first positive electrode slurry was obtained. The second positive electrode active material lithium cobalt oxide (LiCoO 2), conductive agent Super P, and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97:1.4:1.6, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 75wt%. After being stirred evenly by a vacuum mixer, the second positive electrode slurry is obtained. The first positive electrode slurry is coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried at 85°C to obtain a first positive electrode material layer with a thickness of 200μm, and then the second positive electrode slurry is sprayed on the first positive electrode material layer with a spray device, and dried at 85°C to obtain a single-sided coated positive electrode sheet with a second positive electrode material layer thickness of 1μm. After that, the above steps are repeated on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided coated positive electrode material layer. After coating, the positive electrode sheet is cold pressed and cut into a specification of 74mm×866m for standby use. Among them, the compaction density of the positive electrode material layer after cold pressing is 3.2g / cm 3 .
[0099] Example 1-10 to Example 1-18
[0100] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.
[0101] Wherein, when the mass percentage x of the compound of formula I changes, the mass percentage of diethyl carbonate changes accordingly, and the mass percentages of lithium salt, ethylene carbonate and propylene carbonate remain unchanged. The sum of the mass percentages of the compound of formula I, lithium salt, ethylene carbonate, propylene carbonate and diethyl carbonate is 100%.
[0102] Example 2-1
[0103] Except that the electrolyte was prepared according to the following steps in <Preparation of electrolyte>, the rest is the same as Example 1-1.
[0104] <Preparation of Electrolyte>
[0105] In an argon atmosphere glove box with a water content of less than 10 ppm, ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) are mixed to obtain a basic organic solvent, and then lithium hexafluorophosphate is added to the basic organic solvent, dissolved and mixed evenly. Then, the compound of formula I-1 and the compound of formula II tetramethyl divinyl disiloxane are added to obtain a non-aqueous electrolyte. Among them, based on the mass of the non-aqueous electrolyte, the mass percentage of lithium salt is 12.5%, the mass percentage of the compound of formula I is 1%, the mass percentage of tetramethyl divinyl disiloxane is 0.01%, the mass percentage of EC is 20%, the mass percentage of PC is 20%, and the mass percentage of DEC is 46.49%.
[0106] Example 2-2 to Example 2-5
[0107] Except for adding the compound of formula II into the electrolyte and adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 1-1.
[0108] When the mass percentage f of the compound of formula II changes, the mass percentage of diethyl carbonate changes accordingly, and the mass percentages of the compound of formula I, lithium salt, ethylene carbonate and propylene carbonate remain unchanged. The sum of the mass percentages of the compound of formula II, the compound of formula I, lithium salt, ethylene carbonate, propylene carbonate and diethyl carbonate is 100%.
[0109] Example 3-1
[0110] The same as in Example 1-1 except that the electrolyte was prepared as follows in <Preparation of electrolyte>
[0111] <Preparation of Electrolyte>
[0112] In an argon atmosphere glove box with a water content of less than 10 ppm, ethylene carbonate (EC) and diethyl carbonate (DEC) are mixed to obtain a basic organic solvent, and then lithium hexafluorophosphate is added to the basic organic solvent, dissolved and mixed evenly. Then the compound of formula I-1 is added to obtain a non-aqueous electrolyte. Among them, based on the mass of the non-aqueous electrolyte, the mass percentage of lithium salt is 12.5%, the mass percentage of the compound of formula I is 1%, the mass percentage of EC is 5%, and the mass percentage of DEC is 81.5%, and the rest is the same as Example 1-1.
[0113] Example 3-2 to Example 3-7
[0114] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 3-1.
[0115] Wherein, when the mass percentage z of the cyclic carbonate compound changes, the mass percentage of diethyl carbonate changes accordingly, and the mass percentages of the compound of formula I, lithium salt, ethylene carbonate and propylene carbonate remain unchanged. The sum of the mass percentages of the cyclic carbonate compound, the compound of formula I, lithium salt, ethylene carbonate, propylene carbonate and diethyl carbonate is 100%.
[0116] Comparative Example 1 Except for following the steps in <Preparation of positive electrode sheet> and <Preparation of electrolyte>, the rest is the same as Example 1-1.
[0117] <Preparation of positive electrode sheet>
[0118] The first positive electrode active material is lithium manganese oxide (LiMn 2 O 4), conductive agent Super P, and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97:1.4:1.6, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 75wt%. The positive electrode slurry is obtained after being stirred evenly with a vacuum mixer. The positive electrode slurry is coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried at 85°C to obtain a positive electrode material layer with a thickness of 150μm. The above steps are repeated on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided positive electrode material layer. After coating, the positive electrode sheet is cold pressed and cut into a specification of 74mm×866mm for standby use. Among them, the compaction density of the positive electrode material layer after cold pressing is 2.6g / cm 3 .
[0119] <Preparation of Electrolyte>
[0120] In an argon atmosphere glove box with a water content of less than 10 ppm, ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) are mixed to obtain a basic organic solvent, and then lithium hexafluorophosphate is added to the basic organic solvent, dissolved and mixed evenly to obtain a non-aqueous electrolyte. Based on the mass of the non-aqueous electrolyte, the mass percentage of the lithium salt is 12.5%, the mass percentage of EC is 20%, the mass percentage of PC is 20%, and the mass percentage of DEC is 47.5%.
[0121] Comparative Example 2 to Comparative Example 4
[0122] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.
[0123] Wherein, when the mass percentage x of the compound of formula I changes, the mass percentage of diethyl carbonate changes accordingly, and the mass percentages of lithium salt, ethylene carbonate and propylene carbonate remain unchanged. The sum of the mass percentages of the compound of formula I, lithium salt, ethylene carbonate, propylene carbonate and diethyl carbonate is 100%.
[0124] Table 1
[0125] It can be seen from Examples 1-1 to 1-18 and Comparative Examples 1 to 4 that the electrochemical device of the present application embodiment contains an electrolyte comprising a compound of Formula I and a double-layer coated positive electrode sheet, and the mass percentage x of the compound of Formula I is controlled within the range of 0.01% to 5%; x is proportional to the thickness h of the first positive electrode material layer. 1 The ratio x / h 1Controlled within the range of 0.00033 to 0.1, the electrochemical device can have a higher cycle capacity retention rate and nail penetration rate, and at the same time have a lower IMP growth rate, indicating that the electrochemical device of the embodiment of the present application has good cycle performance, storage performance and safety performance. The comparative example does not contain the electrolyte including the compound of formula I and the double-layer coated positive electrode sheet, or x and x / h 1 The value of is not within the scope of this application. The electrochemical device of the comparative example has a lower cycle capacity retention rate and nail penetration rate, and a higher IMP growth rate, indicating that the electrochemical device of the comparative example has poor cycle performance, storage performance and safety performance.
[0126] The thickness of the first positive electrode material layer h 1 It usually affects the cycle performance, storage performance and safety performance of the electrochemical device. It can be seen from Examples 1-1, 1-4 to 1-6 that when h is adjusted 1 When the value of is within the scope of the present application, the electrochemical device can have a higher cycle capacity retention rate and nail penetration rate, and at the same time have a lower IMP growth rate, indicating that the electrochemical device provided by the present application has good cycle performance, storage performance and safety performance.
[0127] The ratio k of the thickness of the first positive electrode material layer to the thickness of the second positive electrode material layer usually affects the cycle performance, storage performance and safety performance of the electrochemical device. It can be seen from Examples 1-1, 1-7 to 1-9 that when the value of k is adjusted within the scope of this application, the electrochemical device can have a higher cycle capacity retention rate and nail penetration rate, and at the same time have a lower IMP growth rate, indicating that the electrochemical device provided by this application has good cycle performance, storage performance and safety performance.
[0128] The type of compound of formula I usually affects the cycle performance, storage performance and safety performance of the electrochemical device. It can be seen from Examples 1-1, 1-10 to 1-13 that when the type of compound of formula I is regulated within the scope of this application, the electrochemical device can have a higher cycle capacity retention rate and nail penetration rate, and at the same time have a lower IMP growth rate, indicating that the electrochemical device provided by this application has good cycle performance, storage performance and safety performance.
[0129] The type and content of the first positive electrode active material and the type and content of the second positive electrode active material usually affect the cycle performance, storage performance and safety performance of the electrochemical device. It can be seen from Examples 1-1, 1-14 to 1-18 that when the type and content of the first positive electrode active material and the second positive electrode active material are regulated within the scope of this application, the electrochemical device can have a higher cycle capacity retention rate and nail penetration rate, and at the same time have a lower IMP growth rate, indicating that the electrochemical device provided by this application has good cycle performance, storage performance and safety performance.
[0130] Table 2
[0131] The content f and type of the compound of formula II usually affect the cycle performance, storage performance and safety performance of the electrochemical device. It can be seen from Examples 1-1, 2-1 to 2-5 that by regulating the content f and type of the compound of formula II within the scope of this application, the chemical stability of the electrolyte can be improved, and the electrochemical device has a higher cycle capacity retention rate and nail penetration rate, and at the same time has a lower IMP growth rate, indicating that the electrochemical device provided by this application has good cycle performance, storage performance and safety performance.
[0132] Table 3
[0133] The type and mass percentage of the cyclic carbonate compound type usually affect the cycle performance, storage performance and safety performance of the electrochemical device. It can be seen from Examples 1-1, 3-1 to 3-7 that by regulating the type and mass percentage z of the cyclic carbonate compound type within the scope of this application, the electrochemical device can have a higher cycle capacity retention rate and nail penetration rate, and at the same time have a lower IMP growth rate, indicating that the electrochemical device provided by this application has good cycle performance, storage performance and safety performance.
[0134] The ratio of the thickness of the first positive electrode material layer to the mass percentage of the cyclic carbonate usually affects the cycle performance, storage performance and safety performance of the electrochemical device. 1 The value of / z is within the scope of the present application, which can enable the electrochemical device to have a higher cycle capacity retention rate and nail penetration rate, and at the same time have a lower IMP growth rate, indicating that the electrochemical device provided by the present application has good cycle performance, storage performance and safety performance.
[0135] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. An electrochemical device comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, The electrolyte comprises at least one compound of formula I: ; in, R 11 and R 12 are independently selected from a hydrogen atom, a halogen atom, a substituted or unsubstituted C1 to C 10 Alkyl, substituted or unsubstituted C2 to C 10 alkenyl, substituted or unsubstituted C2 to C 10 Alkynyl, substituted or unsubstituted C1 to C 10 Alkoxy or substituted or unsubstituted C1 to C 10 When substituted, the substituent is selected from a halogen atom, a C2 to C5 cycloalkyl group or a C6 to C 12 Aromatic group; The X 11 ¯Anionic group is selected from PF6¯, F¯, NO3¯, PO2F2¯, BF4¯, (FSO2)2N¯, F3SO2O¯, , , , , , or Any of; Based on the mass of the electrolyte, the mass percentage of the compound of formula I is x%, 0.01≤x≤5; The positive electrode sheet comprises a positive electrode current collector and a first positive electrode material layer and a second positive electrode material layer located on at least one surface of the positive electrode current collector, wherein the first positive electrode material layer is located between the positive electrode current collector and the second positive electrode material layer, the first positive electrode material layer comprises an Mn element and has a thickness of h1 μm, and the thickness of the second positive electrode material layer is h2 μm, wherein a ratio h1 / h2 of the thickness h1 of the first positive electrode material layer to the thickness h2 of the second positive electrode material layer is k; The x and h1 satisfy the relationship: 0.00033≤x / h1≤0.
1.
2. The electrochemical device according to claim 1, wherein: The electrochemical device satisfies at least one of the following characteristics: (1)30≤h1≤200; (2)0.5≤k≤150; (3) 0.005≤x / h1≤0.
1.
3. The electrochemical device according to claim 1, wherein The compound of formula I includes at least one of the following compounds: 。 4. The electrochemical device according to claim 1, wherein The electrolyte further comprises a silane compound containing an unsaturated bond, wherein the silane compound containing an unsaturated bond is selected from at least one of the compounds of formula II: ; Among them, R 21 , R 22 , R 23 and R 24 are independently selected from a hydrogen atom, a halogen atom, a cyano group, a substituted or unsubstituted C1 to C 10 Alkyl, substituted or unsubstituted C2 to C 10 alkenyl, substituted or unsubstituted C2 to C 10 Alkynyl or substituted or unsubstituted C1 to C 10 Any one of the heteroatom-containing functional groups of 21 , R 22 , R 23 and R 24 Any two groups in can form a ring; 21 , R 22 , R 23 and R 24 At least one of them contains an unsaturated bond; Based on the mass of the electrolyte, the mass percentage of the compound of formula II is f%, 0.01≤f≤1.
5. The electrochemical device according to claim 4, wherein: The compound of formula II includes at least one of tetramethyl divinyl disiloxane, bis(trimethylsilyl) maleate, tetraallylsilane, pentamethyl pentavinyl cyclopentasiloxane, vinyl trimethylsilane, divinyl dimethyl silane, 1,3-dimethyl-1,1,3,3-tetravinyl disiloxane, trivinyl methyl silane, triethyl vinyl silane, allyl triethoxy silane, triethyl silyl acetylene, tetravinyl silane, triacetoxy ethyl silane, tetramethyl tetravinyl cyclotetrasiloxane, diphenyl difluorosilane, 2,4,6-trivinyl-2,4,6-trimethyl cyclotrisiloxane or vinyl triethoxy silane.
6. The electrochemical device according to claim 1, wherein: The first positive electrode material layer includes a first positive electrode active material, and the first positive electrode active material includes at least one of lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium manganese iron phosphate, lithium manganese phosphate or lithium-rich manganese-based material; based on the mass of the first positive electrode material layer, the mass percentage of Mn element in the first positive electrode material layer is y1%, 20≤y1≤60; The second positive electrode material layer includes a second positive electrode active material, and the second positive electrode active material includes at least one of lithium cobalt oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium manganese phosphate, sodium iron phosphate, lithium vanadium phosphate, sodium vanadium phosphate, lithium vanadium oxyphosphate, sodium vanadium oxyphosphate, lithium vanadate, lithium nickel oxide, lithium nickel cobalt manganese oxide, lithium-rich manganese-based material, lithium nickel cobalt aluminum oxide or lithium titanate; based on the mass of the second positive electrode material layer, the mass percentage of Mn element in the second positive electrode material layer is y2%, y1>y2.
7. The electrochemical device according to claim 1, wherein: The first positive electrode material layer includes a first positive electrode active material, which includes at least one of lithium manganese oxide or lithium iron manganese phosphate; the second positive electrode material layer includes a second positive electrode active material, which includes at least one of lithium iron phosphate or lithium nickel cobalt manganese oxide.
8. The electrochemical device according to claim 1 or 2, wherein: The electrolyte further comprises a cyclic carbonate compound, and the mass percentage of the cyclic carbonate compound is z%, based on the mass of the electrolyte, and 5≤z≤40.
9. The electrochemical device according to claim 8, wherein: 1.25≤h1 / z≤30.
10. The electrochemical device according to claim 8 or 9, wherein: The cyclic carbonate compound includes at least one of ethylene carbonate, propylene carbonate or butylene carbonate.
11. An electronic device comprising the electrochemical device according to any one of claims 1 to 10.
Citation Information
Patent Citations
Secondary cell, electronic device, and vehicle
CN113994506A
Secondary battery and electric device
CN115458707A
Electrochemical device and electronic device
CN117577950A
Nonaqueous electrolyte
US20050221188A1
Electrochemical device and electronic device
US20240356022A1